Selective Catalytic Oxidation of Benzyl Alcohol to Benzaldehyde by Nitrates - Xu, Shurui; Wu, Jie; Huang, Peng; Lao, Chunwen; Lai, Hanchao; Wang, Yuxiong; Wang, Zhenyu; Zhong, Guoyu; Fu, Xiaobo; Peng, Feng (Frontiers in Chemistry, 2020)
In this paper, ferric nitrate was used to oxidize benzyl alcohol in a mild condition and demonstrated its better performance compared to HNO3. In the reaction, the conversion rate and product selectivity could be both as high as 95% in N2 atmosphere, while the benzaldehyde yield also reached 85% in air. Similar to Fe(NO3)3·9H2O, the other metallic nitrates such as Al(NO3)3·9H2O and Cu(NO3)2·3H2O could also oxidize the benzyl alcohol with high activity. The applicability of Fe(NO3)3·9H2O for other benzylic alcohol was also investigated, and the reaction condition was optimized at the same time. The results showed the Fe(NO3)3·9H2O would be more conducive in oxidizing benzyl alcohol under the anaerobic condition. The experiments in N2 or O2 atmospheres were conducted separately to study the catalytic mechanism of Fe(NO3)3. The results showed the co-existence of Fe3+ and NO3- will generate high activity, while either was with negligible oxidation property. The cyclic transformation of Fe3+ and Fe2+ provided the catalytic action to the benzyl alcohol oxidation. The role of NO3- was also an oxidant, by providing HNO2 in anaerobic condition, while NO3- would be regenerated from NO in aerobic condition. O2 did not oxidize the benzyl alcohol conversion directly, while it could still be beneficial to the procedure by eliminating the unwelcome NO and simultaneously reinforcing the circulation of Fe2+ and Fe3+, which therefore forms a green cyclic oxidation. Hence, the benzyl alcohol oxidation was suggested in an air atmosphere for efficiency and the need of green synthesis.